Development of a Rapid Real-Time PCR Method as a Tool To Quantify Viable Photobacterium phosphoreum Bacteria in Salmon (Salmo salar) Steaks - Mace, Sabrina; Mamlouk, Kelthoum; Chipchakova, Stoyka; Prévost, Herve; Joffraud, Jean-Jacques; Dalgaard, Paw; Pilet, Marie-France; Dousset, Xavier (Applied and Environmental Microbiology, 2013)
International audience A specific real-time PCR quantification method combined with a propidium monoazide sample treatment step was developed to determine quantitatively the viable population of the Photobacterium phosphoreum species group in raw modified-atmosphere-packed salmon. Primers were designed to amplify a 350-bp fragment of the gyrase subunit B gene (gyrB) of P. phosphoreum. The specificity of the two primers was demonstrated by using purified DNA from 81 strains of 52 different bacterial species. When these primers were used for real-time PCR in pure culture, a good correlation (R-2 of 0.99) was obtained between this method and conventional enumeration on marine agar (MA). Quantification was linear over 5 log units as confirmed by using inoculated salmon samples. On naturally contaminated fresh salmon, the new real-time PCR method performed successfully with a quantification limit of 3 log CFU/g. A correlation coefficient (R-2) of 0.963 was obtained between the PCR method and classic enumeration on MA, followed by identification of colonies (290 isolates identified by real-time PCR or by 16S rRNA gene sequencing). A good correlation with an R-2 of 0.940 was found between the new PCR method and an available specific conductance method for P. phosphoreum. This study presents a rapid tool for producing reliable quantitative data on viable P. phosphoreum bacteria in fresh salmon in 6 h. This new culture-independent method will be valuable for future fish inspection, the assessment of raw material quality in fish processing plants, and studies on the ecology of this important specific spoilage microorganism.